2012
DOI: 10.1155/2012/983640
|View full text |Cite
|
Sign up to set email alerts
|

Microglia, Alzheimer's Disease, and Complement

Abstract: Microglia, the immune cell of the brain, are implicated in cascades leading to neuronal loss and cognitive decline in Alzheimer's disease (AD). Recent genome-wide association studies have indicated a number of risk factors for the development of late-onset AD. Two of these risk factors are an altered immune response and polymorphisms in complement receptor 1. In view of these findings, we discuss how complement signalling in the AD brain and microglial responses in AD intersect. Dysregulation of the complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 126 publications
0
58
0
4
Order By: Relevance
“…When activated, microglia proliferate, form nodules to surround areas of damage, and secrete cytokines/chemokines to recruit immune cells (47)(48)(49)(50)(51)(52)(53). Despite different triggering events, microglia activation is a major characteristic of neurodegenerative conditions, including Alzheimer's disease, Parkinson's diseases, traumatic brain injury, and multiple sclerosis (54)(55)(56)(57). Similarly, when activated, astrocytes proliferate and are potent producers of cytokines/chemokines (51).…”
Section: Discussionmentioning
confidence: 99%
“…When activated, microglia proliferate, form nodules to surround areas of damage, and secrete cytokines/chemokines to recruit immune cells (47)(48)(49)(50)(51)(52)(53). Despite different triggering events, microglia activation is a major characteristic of neurodegenerative conditions, including Alzheimer's disease, Parkinson's diseases, traumatic brain injury, and multiple sclerosis (54)(55)(56)(57). Similarly, when activated, astrocytes proliferate and are potent producers of cytokines/chemokines (51).…”
Section: Discussionmentioning
confidence: 99%
“…[1] Microglial cells perform a variety of different functions within the CNS related to the immune response and the maintenance of cellular homeostasis. Much interest has focused on the role of microglia in neurodegenerative diseases (particularly Alzheimer's disease (AD)) in recent times due to an increasing number of genetic and biomarker discovery programs and growing evidence to suggest that inflammation has a role in disease pathogenesis.…”
mentioning
confidence: 99%
“…Some research articles indicated that the microglial activity could be manipulated by the complement factors towards protective or harmful [18]. Various research groups tried to show the role of complement system in Alzheimer's disease and also trying to find out the suitable therapeutic approaches targeting complement system as mentioned in Table 2.…”
Section: Immunotherapeutic Approachmentioning
confidence: 99%
“…The purpose of this review article is to brief cellular neuroimmunological aspects of AD, describes advances in the use of immunotherapy for treatment of AD and highlights ongoing efforts to develop novel therapies. complement system in AD [18]. There are many possible approaches which can Neurons can generate the inflammatory molecules and can serve as source of complement systems and others.…”
Section: Introductionmentioning
confidence: 99%